Migrant patients’ satisfaction with health care services: a comprehensive review (Italian Journal of Public Health, 2010)
Objectives and methods: We sought to determine immigrants’ level of satisfaction with health care servicesin western developed countries. A comprehensive literature search was conducted to identify all relevantstudies that assessed patient satisfaction among this population subgroup. As the research encountereddifferent methods and settings, results were synthesized in a narrative form.Results and conclusions: The search process yielded 54 potentially relevant (published) studies. 26 of themwere excluded for reasons presented in the section Exclusion criteria. The remaining 28 were retained foranalysis. Usually, immigrant patients showed lower satisfaction levels with western health services.
Keywords: migrants; foreigners; patient satisfaction